Translational diffusion coefficients and hydrodynamic radii of normal corn starch in aqueous media from asymmetrical flow field-flow fractionation experiments - Juna, Shazia; Huber, Anton (Diffusion Fundamentals, 2011)
Starch is a highly disperse material with broad distributions of molecular sizes and geometries. Its dissolution in aqueous media is difficult to achieve and it tends to form aggregates through both inter- and intra-molecular interactions. Asymmetrical flow field-flow fractionation (AF4) is a suitable technique for the separation of such macromolecular and colloidal systems. A major advantage of AF4 is the direct correlation of translational diffusion coefficients with retention time and experimental parameters. In this article, the hydrodynamic and diffusive mobility of normal corn starch dissolved in 0.035 M KSCN was investigated by systematically varying the cross flow rates (applied forces); the translational diffusion coeffcients for normal corn starch in aqueous medium were found to range between 9.9 x 10-9 cm2/s and 2.5 x 10-7 cm2/s with varying Fcr rates. Diffusion coefficient ranges shifted to higher diffusion co-efficient values at higher cross flow rates (applied forces). This behaviour, which may be attributed to the increased retention of very large starch molecules/particles at high Fcr rates, is further confirmed by the decrease in apparent molar mass and mass recovery values.